Correlation Of Schmidt Hammer Rebound Numbers And Knocking Ball Stiffness Parameters For Sedimentary And Metasedimentary Rocks - Ares, Mohammad Danial Farhan Mohamad (Universiti Sains Malaysia, 2022)
One of the most important rock properties is intact rock strength. The strength of an intact rock block material is determined by intact rock strength, which influences a fraction of the strength of a rock mass. In the context of studies for slope stability assessment, the intact rock strength of a rock mass has been assessed using a variety of different methods. In this study, correlation is established between the methods of the data acquisition of the intact rock properties. The data acquisition is done by performing two in-situ tests which are Schmidt Hammer and Knocking Ball tests. The Schmidt Hammer test is the standardised approach used in the industry as it is an effective index apparatus which is easy to use and handle, however, it may encounter a difficulty when assessing a wide range of rock strength especially in the lower range. Meanwhile, the Knocking Ball test which is based on the Hertz theory can be applied to a wider range of rock strength as it is more sensitive equipment. These two methods are correlated using their rebound numbers and stiffness parameters. In addition, the UCS of the rebound number will also be determined to be correlated with the Young’s modulus of the stiffness parameters. All the correlations established are good and positive as it achieved the desired results where the coefficient of the correlation, R2 is greater than 0.5. The two analyses are compared to demonstrate the strengths and weaknesses of each approach employed in this study to assess the properties of intact rocks.